CoEPinKB: Evaluating Path Search Strategies in Knowledge Bases - Jiménez, Javier Guillot; Paes Leme, Luiz André P.; Casanova, Marco A. (Journal of the Brazilian Computer Society, 2022)
A knowledge base, expressed using the Resource Description Framework (RDF), can be viewed as a graph whose nodes represent entities and whose edges denote relationships. The entity relatedness problem refers to the problem of discovering and understanding how two entities are related, directly or indirectly, that is, how they are connected by paths in a knowledge base. Strategies designed to solve the entity relatedness problem typically adopt an entity similarity measure to reduce the path search space and a path ranking measure to order and filter the list of paths returned. This article presents a framework, called CoEPinKB, that supports the empirical evaluation of such strategies. The proposed framework allows combining entity similarity and path ranking measures to generate different path search strategies. The main goals of this article are to describe the framework and present a performance evaluation of nine different path search strategies.